Structural model of resilience based on parental support: the mediating role of hope and active coping - Hadis Cheraghian; Khadije Moradian; Tahere Nouri (BMC Psychiatry, 2023)
Abstract Resilience is an essential trait in the academic and non-academic lives of students that has been associated with positive psychological and non-psychological outcomes. Given the importance and role of resilience, the main goal of this study was to create a structural model of resilience based on parental support and emphasizing the mediating role of hope and coping. The research design was correlational in nature and used structural equation modeling (SEM). The population of this study included high school students in Tehran city in 2019–2020 school year, and the sample consisted of 560 students selected by cluster sampling method. By applying Spearman correlation analysis and structural equation modeling, a significant relationship between hope, coping, resilience, and parental support was found. Both the SEM measurement and structural models provided a good fit. The significant findings of the present study include the direct and significant effect of parental support on resilience. The indirect and significant effect of parental support on resilience through the mediating role of hope and coping was also confirmed. Overall, the results of this study show that the effect of parental support on resilience can be improved by promoting hope and coping styles.